Productivity of the Seagrass Enhalus acoroides (L.f.) Royle in the Littoral Zone of Guang-Guang, Mati, Davao Oriental - Ann Cherry Cereno; Ariel Eballe; Lea AngSinco-Jimenez (Davao Research Journal)
The productivity, growth rate, population density and some physico-chemical parameters affecting Enhalus acoroides in the littoral zone of Guang-guang, Mati, Davao Oriental was conducted from November 1996 to January 1997. Productivity of E. acoroides was detennined using the stabbing technique. Estimated mean shoot density ranged from 16.15 to 28.9 shoot/m2. Growth rate ranged from 1.34 to 1.49 cm/d while shoot biomass ranged from 0.876 to 1.874 g/shoot. Standing crop of the species averaged at around 155,052.00 to 531,760.00 g/m. Results obtained from areal shoot biomass ranged from 84.465 to 192.416 g/m2. Production rate values averaged from 193.82 to 607 g/m2/y. Correlation tests between growth and different physicochemical parameters were also' obtained.